2021
DOI: 10.1002/mrm.28851
|View full text |Cite
|
Sign up to set email alerts
|

End‐to‐end deep learning nonrigid motion‐corrected reconstruction for highly accelerated free‐breathing coronary MRA

Abstract: To develop an end-to-end deep learning technique for nonrigid motioncorrected (MoCo) reconstruction of ninefold undersampled free-breathing wholeheart coronary MRA (CMRA). Methods: A novel deep learning framework was developed consisting of a diffeomorphic registration network and a motion-informed model-based deep learning (MoDL) reconstruction network. The registration network receives as input highly undersampled (~22×) respiratory-resolved images and outputs 3D nonrigid respiratory motion fields between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 45 publications
0
35
0
Order By: Relevance
“…The registration loss and reconstruction loss are designed for each unrolled iteration to train the proposed GRDRN. For registration, previous works ( 32 , 33 ) have demonstrated that by constructing the MSE loss based on the fully sampled ground truth images, it is possible to learn the motion from undersampled images. Therefore, while the input to GRN is the undersampled or intermediate reconstructed images, the registration loss as defined in Equation (1) for the k -th iteration is calculated based on the fully sampled ground truth dynamic images .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The registration loss and reconstruction loss are designed for each unrolled iteration to train the proposed GRDRN. For registration, previous works ( 32 , 33 ) have demonstrated that by constructing the MSE loss based on the fully sampled ground truth images, it is possible to learn the motion from undersampled images. Therefore, while the input to GRN is the undersampled or intermediate reconstructed images, the registration loss as defined in Equation (1) for the k -th iteration is calculated based on the fully sampled ground truth dynamic images .…”
Section: Methodsmentioning
confidence: 99%
“…The motion-augmented dynamic sequence is then incorporated into the reconstruction network to improve the reconstruction performance. For GRN, we employ the self-supervised deep learning registration model, which is more efficient and robust than traditional motion estimation algorithms in the presence of undersampling artifacts ( 32 , 33 ). To the best of our knowledge, this is the first work that embeds groupwise registration network into the deep learning reconstruction framework to exploit the full temporal information of the acquired data to aid in the dynamic MRI reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…The estimated motion fields are then used to enhance the data consistency and exploit the information of all motion resolved states to reconstruct images of the body trunk. In the context of coronary MRI, a motion-informed MoDL network was proposed [11], using diffeomorphic motion fields estimated from the zero-filled images using a UNet and subsequent scaling and squaring layer. These motion fields are then embedded into the data consistency layer, solved via the conjugate gradient algorithm as in MoDL.…”
Section: ) Motionmentioning
confidence: 99%
“…Recently, deep learning methods have emerged as a powerful tool for solving many inverse problems in computational MRI. Among these, MRI reconstruction for accelerated acquisitions remains the most wellstudied [6][7][8], along with several strategies for quantitative MRI [9], motion [10,11] and other non-linear physical models [12,13]. Out of a plethora of approaches for these problems, physics-driven methods have emerged as the most well-received deep learning techniques by the MRI community due to their incorporation of the MR domain knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…However, the non-linear nature of the problems to be solved leads to long reconstruction times, in addition to the parameter tuning required for an optimal regularization. Several DL-based alternatives have been proposed to overcome these limitations and enable not only highly accelerated acquisitions in short reconstruction times (32,33,(46)(47)(48)(49)(50)(51), but also a wide range or AI-aided solutions for CMR segmentation (40) and analysis or outcome prediction (52,53) among others.…”
Section: Deep Learning In Cardiac Mrmentioning
confidence: 99%